1984
DOI: 10.1037/0278-7393.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic category search and its transfer.

Abstract: Experiments examined practice and transfer effects in consistently mapped (CM) and variably mapped (VM) semantic search. Experiment 1a examined improvements in reaction time in detecting words from a category as a function of the number of exemplars (4-12) in the category. All CM conditions showed improvement, but there was no significant effect of the number of exemplars. Experiment 1b examined the extent to which training on a subset of exemplars transferred to untrained members of the category. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
141
2
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 16 publications
16
141
2
3
Order By: Relevance
“…The data appear to support and extend the context activation hypothesis proposed by Schneider and Fisk (1984) as an important locus of CM training. The context activation framework assumes that consistent exposure to the training context is a critical factor leading to performance improvement.…”
Section: Amount Of Consistent Practicesupporting
confidence: 67%
See 3 more Smart Citations
“…The data appear to support and extend the context activation hypothesis proposed by Schneider and Fisk (1984) as an important locus of CM training. The context activation framework assumes that consistent exposure to the training context is a critical factor leading to performance improvement.…”
Section: Amount Of Consistent Practicesupporting
confidence: 67%
“…Fisk and Rogers (1988) found that, in the absence of traditional consistency, context can play an important role in facilitating performance. In addition, the Fisk and Rogers data supported the suggestion that context can also be important for completely consistent tasks (e.g., see Schneider and Fisk, 1984).…”
Section: Contextual Change and Skill Acquisition In Visual Searchsupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, even if retrieval is required to set the stored algorithm in place, the computation of the algorithm may fall beyond the boundaries of retrieval (at least according to those theorists who argue for a qualitative distinction between memory retrieval and algorithm computation). 5 Support for algorithm-based automaticity has come mainly from skill development studies in which the benefits of practice with consistent algorithms transferred to data that were never encountered during practice (Carlson & Lundy, 1992;Kramer, Strayer, & Buckley, 1990;Schneider & Fisk, 1984;Smith & Lerner, 1986). These benefits were evident in increased speed and efficiency.…”
Section: Algorithm Strengthening Viewmentioning
confidence: 99%